2016
DOI: 10.1021/acs.orglett.6b02865
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Synthesis of N–C Axially Chiral Mebroqualone and Its Derivatives through Reductive Asymmetric Desymmetrization

Abstract: In the presence of (R)-DTBM-SEGPHOS-Pd(OAc) catalyst, treatment of various 3-(2,6-dibromophenyl)quinazolin-4-ones with NaBH gave optically active N-C axially chiral quinazolinone (mebroqualone) derivatives through reductive asymmetric desymmetrization (enantioselective monohydrodebromination) followed by kinetic resolution of the resulting monobromophenyl products (up to 99% ee). The enantioselectivity strongly depended on the substituent (R) at the C4'position, amount of NaBH, and reaction temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…Until recently, the preparation of these optically active N-C nonbiaryl atropisomers still depends largely on the chiral resolution and diastereoselective synthesis using chiral pool precursors 1517 . Only few strategies for catalytic atroposelective construction of N-C nonbiaryl atropisomers exist and mainly consist of enantioselective cyclization 1820 , N-functionalization 2127 , and desymmetrization 2830 of the existing achiral N-C bond. The direct catalytic enantioselective method to build a new chiral N-C bond to form nonbiaryl N-C atropisomers still has significant synthetic challenges and has attracted great interest.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, the preparation of these optically active N-C nonbiaryl atropisomers still depends largely on the chiral resolution and diastereoselective synthesis using chiral pool precursors 1517 . Only few strategies for catalytic atroposelective construction of N-C nonbiaryl atropisomers exist and mainly consist of enantioselective cyclization 1820 , N-functionalization 2127 , and desymmetrization 2830 of the existing achiral N-C bond. The direct catalytic enantioselective method to build a new chiral N-C bond to form nonbiaryl N-C atropisomers still has significant synthetic challenges and has attracted great interest.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] In addition, modification of the existing biaryl structures enables access to enantio-enriched atropisomers via either a desymmetrization reaction or (dynamic) kinetic resolution (Scheme 1D). [16][17][18][19][20][21][22][23][24][25] Furthermore, the construction of benzylic center chirality, followed by center-to-axial chirality transfer aromatization is also an effective approach to access enantio-enriched biaryl atropisomers. 26,27 Recently, there have been a number of reports on organocatalyzed asymmetric atropisomer synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…With these results in hand, we focused our attention on the structural generality of this approach, studying possible effect of various substituents on the magnitude of the observed SDE and the preparative efficiency in terms of the enantiomeric purifications. To this end, we prepared seven, previously reported derivatives 1 b – d , f , g presented in Figure . All experiments were conducted under the same chromatographic conditions developed for the original mebroqualone 1 a .…”
Section: Resultsmentioning
confidence: 99%
“…Although direct observation of high‐order species in solution is not possible, it was shown that a very sound idea about a preference for homo‐/heterochiral molecular associations can be obtained by considering the crystallographic structures of racemic and enantiomerically pure compounds . To this end, we performed X‐ray studies of parent compound enantiomerically pure mebroqualone ( P )‐ 1 a (99 % ee ) and its racemic form ( P / M )‐ 1 a ; the data are presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation